Platelet-Rich Fibrin (PRF) effectiveness in maxillary sinus lift: case report (Research, Society and Development, 2021)
Incluir o resumo em inglês. The sinus lift surgery is a common procedure with predictable outcomes in dental practice. There is a great diversity and availability of bone substitutes. Hence, the materials to fill the sinus cavity have been studied and searched due to the requirement for a patterned material with the capacity of bone formation in a short period of time. Platelet-rich fibrin (PRF) is one of those materials that, due to its autologous feature, has low cost and a simplified protocol. Therefore, it has been widely used and has shown excellent results. Considering the benefits attributed to PRF, the aim of this study was to evaluate the effectiveness of its association with a bone substitute in maxillary sinus lift surgeries, compared to the exclusive use of that same substitute. This split-mouth study was evaluated clinically and histologically. Despite the histological indifferences between the samples analyzed, the association of PRF with bone substitute improved bone quality in the grafted region when compared to the side where only the bone substitute was used.